Hypermarket Consumer Behavior In Malaysia - Yeng, Lim Chow (2003)
This study examines the hypermarket consumer behavior in Malaysia. This paper has developed a chart called "Retailed Loyalty Chart" based on Oliver's Four Stage Loyalty Model.